R-annihilator-Coessential and R-annihilator-Coclosed Submodules - Ibrahim, Omar K.; Elewi, Alaa A. (Iraqi Journal of Science, 2020)
Let be a unitary left R-module on associative ring with identity. A submodule of is called -annihilator small if , where is a submodule of , implies that ann( )=0, where ann( ) indicates annihilator of in . In this paper, we introduce the concepts of -annihilator-coessential and - annihilator - coclosed submodules. We give many properties related with these types of submodules.